THE INFLUENCE OF TRANSFORMATIONAL AND TRANSACTIONAL LEADERSHIP, AND ALSO MOTIVATION ON EMPLOYEE’S PERFORMANCE - Marlis Nur; Arbia Ali; Yusuf .; Chamariyah . (Journal of Management and Business, 2015)
This study aims to analyze the effect of transformational and transactional leadership style and also motivation on the performance of employees in the public works agency at Kolaka district. The study was conducted using a survey of 50 civil servants Kolaka district department of public works. The results showed that transformational and transactional leadership style, and also motivation influence the employee’s performance.